Analysis of factors influencing substance use craving among Chinese substance users - Guo, Huijuan; Wang, Jizhi; Wang, Siyuan; Zhou, Jiansong; Wang, Xiaoping (Frontiers in Psychiatry, 2022)
Background Substance use has been a serious public safety issue. It not only affects the users’ physical and mental health but is also detrimental to social stability. To improve our understanding of this issue, the present study looked to examine the factors influencing substance use craving and develop interventions to reduce craving and relapse among substance users. Materials and methods A total of 502 substance users were included in this study. Socio-demographic characteristics and substance use-related characteristics were recorded using self-developed forms. With regard to psychological traits, we used the self-esteem scale, the experience of shame scale, and the revised Cheek and Buss shyness scale to assess the self-esteem, shame, and shyness of substance users, respectively. The degree of substance use craving of substance users was assessed using the visual analog scale (VAS). Data were analyzed using independent samples T-test, Pearson correlation analysis, and multiple linear regression analysis, as appropriate. Results The majority of the substance users were unmarried, employed, and with lower education levels. For substance use-related characteristics, the age of first use was 27.52 ± 8.30 years and the duration of substance use was 12.29 ± 7.72 years. The scores of their self-esteem, shame, and shyness were 25.65 ± 3.19, 57.26 ± 7.82, and 37.8 ± 7.13, respectively. All substance users rated the intensity of their substance use cravings using the VAS, which showed that the mean score was 2.83 ± 1.87. Multiple linear regression analysis showed that substance use craving was positively associated with the frequency of substance use (β = 0.186, P < 0.001), times of substance rehabilitation (β = 0.128, P = 0.003), shyness (β = 0.211, P < 0.001), and shame (β = 0.091, P = 0.033), and negatively associated with self-esteem (β = –0.117, P = 0.008). Conclusion Factors and psychological traits related to substance use are important to account for substance use craving and relapse. Thus, our findings are helpful for a better understanding of the extent of substance use cravings among users and the selection of appropriate interventions to control the craving and relapse.